Frequency of enterovirus in patients with suspected bacterial meningitis in Turkey [Türkiye’de bakteriyel menenjitten şüphelenilen hastalarda enterovirüs sikliği] - (:unkn) unknown (Nobelmedicus, 2016)
Objective: Enteroviruses are responsible for the majority of cases of aseptic meningitis. Among these, the human parechoviruses (HPeV) have recently been recognised as important contributors. Discrimination between bacterial and viral meningitis is important for proper treatment and prognosis; however, this distinction is not always possible based on clinical presentation because viral meningitis can mimic bacterial meningitis. The aim of this study was to investigate the frequency of enterovirus and HPeV infection in cerebrospinal fluid (CSF) samples collected from children diagnosed with bacterial meningitis but negative for bacteria in Turkey between 2006 and 2009. Material and Method: CSF samples were collected from children with suspected bacterial meningitis from 37 clinical centres in Turkey. Among 1,460 CSF samples available, 1,184 were negative for bacteria and were included in the study. Enteroviral and HPeV RNA were detected in CSF samples by rRT-PCR, and specific genotypes were identified by direct sequencing of the VP1 region. Results: Enteroviruses were detected in 13 (1%) of the 1,184 CSF specimens analysed and included echovirus 14 (n=1), echovirus 9 (n=1), coxsackievirus B4 (n=1), and unknown serotype (n=10). No HPeVs were detected. Conclusion: Neither clinical nor CSF laboratory criteria routinely used to diagnose bacterial meningitis can definitively rule out viral aetiology, so viral infections should be considered during meningitis surveillance and in patient care. © 2016, Nobelmedicus. All rights reserved.
Keywords: Bacterial meningitis; Enteroviral meningitis; Enterovirus; Human parechovirus